1998
DOI: 10.1084/jem.187.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Functional Separation of Pseudopod Extension and Particle Internalization during Fcγ Receptor–mediated Phagocytosis

Abstract: Receptors for the Fc portion of immunoglobulin (Ig)G (FcγR) mediate phagocytosis of IgG-opsonized particles by a process that can be divided into four major steps: receptor–ligand binding, pseudopod extension, internalization, and lysosomal fusion. We have expressed single classes of FcγR in COS fibroblasts to examine the structural determinants necessary to complete the four steps of phagocytosis. Using phase contrast, fluorescence, confocal, and electron microscopy we have demonstrated that FcγR-expressing C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 43 publications
6
59
1
Order By: Relevance
“…Based on this divergence and assuming an inhibitory role for human CD47, human macrophages might be expected to effi ciently phagocytose opsonized sheep red blood cells (RBCs), which is certainly consistent with years of data showing sheep RBCs are readily phagocytosed by human macrophages ( Lowry et al, 1998 ;Botelho et al, 2000 ;Cooney et al, 2001 ). We show below that human-CD47 can inhibit P hagocytosis of foreign cells or particles by macrophages is a rapid process that is ineffi cient when faced with " self " cells that display CD47 -although signaling mechanisms in self-recognition have remained largely unknown.…”
Section: Introductionmentioning
confidence: 52%
“…Based on this divergence and assuming an inhibitory role for human CD47, human macrophages might be expected to effi ciently phagocytose opsonized sheep red blood cells (RBCs), which is certainly consistent with years of data showing sheep RBCs are readily phagocytosed by human macrophages ( Lowry et al, 1998 ;Botelho et al, 2000 ;Cooney et al, 2001 ). We show below that human-CD47 can inhibit P hagocytosis of foreign cells or particles by macrophages is a rapid process that is ineffi cient when faced with " self " cells that display CD47 -although signaling mechanisms in self-recognition have remained largely unknown.…”
Section: Introductionmentioning
confidence: 52%
“…When the vacuole contains active Fc␥RIIB1 or B2 receptors, fusion with lysosomes and acidification develop (24). Importantly, unlike Fc␥RIIA, the B1 and B2 isoforms are unable to trigger phagocytosis of IgG-coated inert particles, such as RBC (10,40,41). This implies that signals generated by interaction of Toxoplasma with other cellular components are required for Fc␥RIIB1 or B2-induced phagosomal formation and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The ␥-chain cytoplasmic domain contains immunoreceptor tyrosine-based activation motifs (ITAMs) and the ␥-chain cytoplasmic domain is both necessary and sufficient for Fc␥RI␣-induced functions (33,34). Biochemical studies have shown that both cross-linking of Fc⑀RI␣-␥-chain complex and the Fc␥RI␣-␥-chain complex result in activation of Src family kinases and the tyrosine kinase p72 Syk (4,(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%